Impact and perception of learning by teaching activities among university students - de Obesso, María de las Mercedes; Pérez Rivero, Carlos Alberto; Cardona Herrero, Sergio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Teaching methodologies have been adapting to changes in society, from learning in which the student plays a more passive role and is limited to listening to a lecture, to more active learning, using methodologies such as active learning, flipped learning, learning by teaching, role play, etc. This research analyses the students’ perception of their learning with the use of the Learning by Teaching methodology, working with a sample of 196 students of Bachelor’s Degrees in Business Administration and Management, Marketing and Digital Business.